Analysis of Atmospheric Aerosols Using the Lisbon Nuclear Micropore - Rita, E. M. (2001)
The nuclear microprobe installed at Instituto Tecnológico e Nuclear, in Lisbon, was used in the analysis of aerosols collected at the Azores islands. Samples from two different aerosol groups were analysed. One referred to aerosols that were carried from North America and the other one contained aerosols that were carried from the Sahara desert and crossed over Europe. Coarse and fine fractions were analysed for each aerosol group and two-dimensional elemental maps were constructed, which allowed the identification of several individual particles. For particles of interest, elemental spatial correlations and dimensions were determined and point analysis was also carried out (depth information was achieved by fitting Rutherford backscattering spectra). Some of these particles are quite interesting. For instance, in the fine fraction of the aerosols that were carried from North America, particles were found with Cu and Cl in the atomic proportion 1:2 and with dimensions 15 x 15 x 15 μm³, and in the corresponding coarse fraction a particle with K and S was identified, with dimensions 28 x 35 x 30 μm³. Some differences were found between the aerosols groups. One example of these are Ti particles (fine fraction) and Rb (coarse fraction) that were identified in one group (Sahara desert and Europe), but not in the other.